2020
DOI: 10.1093/jn/nxaa016
|View full text |Cite
|
Sign up to set email alerts
|

Increased Iron Status during a Feeding Trial of Iron-Biofortified Beans Increases Physical Work Efficiency in Rwandan Women

Abstract: Background Iron-biofortified staple foods can improve iron status and resolve iron deficiency. However, whether improved iron status from iron biofortification can improve physical performance remains unclear. Objective This study aimed to examine whether changes in iron status from an iron-biofortified bean intervention affect work efficiency. Methods A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…There is substantial evidence proving the efficacy and effectiveness of biofortified crops in increasing micronutrient intake and improving health status in humans [81][82][83][84][85][86][87][88][89]. Hitherto, only two effectiveness studies have been conducted with biofortified crops, both assessing provitamin A biofortified sweet potato.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence proving the efficacy and effectiveness of biofortified crops in increasing micronutrient intake and improving health status in humans [81][82][83][84][85][86][87][88][89]. Hitherto, only two effectiveness studies have been conducted with biofortified crops, both assessing provitamin A biofortified sweet potato.…”
Section: Discussionmentioning
confidence: 99%
“…A study with high iron beans (HIB) and normal beans was carried out with young women in Rwanda, most of whom were iron deficient or anemic. After four and a half months the high iron bean group showed a statistically greater increase in hemoglobin (3.8 g/L), log serum ferritin (0.1 log µgr/L) and total body iron (0.5 mg kg −1 ) (Haas et al, 2016), superior cognitive ability (Murray-Kolb et al, 2017), increased neuron activity (Wenger et al, 2019), and superior work capacity (Luna et al, 2020). In a trial involving Mexican school children age 6-10, the effect of high iron beans on transferrin receptor was narrowly not significant (p = 0.054) (Finkelstein et al, 2019).…”
Section: Bioefficacy Of Biofortified Beansmentioning
confidence: 99%
“…Studies have also shown that consumption of biofortified crops resulted in significant improvements in functional, cognitive, and health outcomes such as improved memory and ability to pay attention (36,37) and improved reaction time (37). For iron-biofortified crops, studies have found improved ability to do every day physical tasks, also known as work efficiency (38). For vitamin A-biofortified crops, research has identified reductions in prevalence and duration of diarrhoea for children under five (39); protection from oxidative stress, chronic diseases, and age-related retinal degeneration (30); improved ability to see in dim light (40); and improved vitamin A content of breast milk (41).…”
Section: Biofortificationmentioning
confidence: 99%